Gambaran Lingkungan Fisik dan Status Gizi Penderita Tuberculosis Paru di Poli Paru RSU Ngudi Waluyo Wlingi Periode Desember 2014 - Enik Sulistyowati (Journal of Ners and Midwifery, 2015)
Pulmonary Tuberculosis (TB) is an infectious disease that still become a problem in the world. In Indonesia, pulmonary TB become one of the major public health problem and has yet to be handled despite tight TB control efforts through government programs. This study aimed to describe the physical environment and the nutritional status of patients with pulmonary TB in the lungs RSU Poly Ngudi Waluyo Wlingi. This was a descriptive study, the subject of the research was pulmonary TB patients in RSU Ngudi Waluyo Wlingi, Blitar. Data obtained by using questionnaires and direct observations on nutritional status. There were 40 subjects, 67.3% were male sex, 20%, of the respondents came from Gandusari region, 37.5% were aged between 36–45 years, 45% of respondents had elementary education, 37.5% working 37.5% Farmers and private work. Physical environment or home environment showed results better home lighting 77.5%, 82.5% home ventilation was not good, the density of residents 90% was not good and 90% good home floor. The state of nutritional status shows 60% BMI in the category thin. This study shows that patients with pulmonary TB in the lungs RSU Poly Ngudi Waluyo Wlingi, have homes that did not meet health requirements, especially in home ventilation components and occupant density, but it also had an excellent nutritional status was not indicated by the majority of BMI into the category of thin.